2010
DOI: 10.1038/nrneph.2010.124
|View full text |Cite
|
Sign up to set email alerts
|

The suffocating kidney: tubulointerstitial hypoxia in end-stage renal disease

Abstract: Chronic kidney disease (CKD) is characterized by irreversible pathological processes that result in the development of end-stage renal disease (ESRD). Accumulating evidence has emphasized the important role of chronic hypoxia in the tubulointerstitium in the final common pathway that leads to development of ESRD. The causes of chronic hypoxia in the tubulointerstitium are multifactorial and include mechanisms such as hemodynamic changes and disturbed oxygen metabolism of resident kidney cells. Epidemiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
228
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(240 citation statements)
references
References 128 publications
1
228
0
7
Order By: Relevance
“…Under basal conditions, renin produced by juxtaglomerular cells is sufficient to main BP and intravascular volume (71). Upon prolonged threat to volume homeostasis (i.e., through exposing mice to a low salt diet and ACE inhibitors) additional cells along afferent arterioles express renin, in angiotensinogen-deficient mice renin is even expressed by fibroblasts (pericytes) all through the kidney cortex (80,81). Models of CKD are also associated with recruitment of additional renin-producing cells.…”
Section: Reninmentioning
confidence: 99%
“…Under basal conditions, renin produced by juxtaglomerular cells is sufficient to main BP and intravascular volume (71). Upon prolonged threat to volume homeostasis (i.e., through exposing mice to a low salt diet and ACE inhibitors) additional cells along afferent arterioles express renin, in angiotensinogen-deficient mice renin is even expressed by fibroblasts (pericytes) all through the kidney cortex (80,81). Models of CKD are also associated with recruitment of additional renin-producing cells.…”
Section: Reninmentioning
confidence: 99%
“…The loss of pericytes, as they transform to myofibroblasts, contributes to loss of the interstitial capillary network, otherwise known as peritubular capillary rarefaction and may play a major role in the development of hypoxia, oxidative stress and progressive tubular cellular injury and fibrosis. 77,78,81,96 Histological studies evaluating human kidney tissue have demonstrated that areas of renal fibrosis and reduced peri-tubular capillary density located together. 97,98 Hypoxia is a recognized final common pathway for the progression of CKD (see below).…”
Section: Renal Inflammation and Fibrosis: The Kidney's Response To Inmentioning
confidence: 99%
“…Reduced renal oxygenation due to the effects of vasoconstriction may manifest before the capillary rarefaction which is identified as part of renal fibrosis. 96,129 In medullary interstitial cells, Ang II has been shown to activate hypoxia inducible factor (HIF-1α) via reactive oxygen species (ROS) generation and in vivo medullary interstitial cells from kidneys perfused with Ang II stain positively for both HIF-1α and αSMA. These findings together link Ang II to both hypoxia and oxidative stress mediated renal fibrosis mechanisms.…”
Section: Activation Of the Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%
“…This fibrosis, in turn, aggravates hypoxia by increasing the distance between capillaries and tubular epithelial cells, leading to reduced oxygen diffusion efficiency. 97 Consequently, hypoxia and tubulointerstitial fibrosis form a pathologic cycle that results in the progression of CKD (figure 1). 242 The cycle is exacerbated by hypoxiainducing gene-activating histone modifications that up-regulate expression of endothelin 1, thus, reducing oxygen delivery to the kidney by vasoconstriction.…”
Section: Repeated Episodes Of Acute Kidney Injurymentioning
confidence: 99%
“…Subsequently, this theory has been validated by numerous studies. [89][90][91][92][93][94][95][96][97][98][99] Particularly informative have been recent experiments where kidney oxygen tension has been reduced with dinitrophenol without affecting markers of oxidative stress. Under these circumstances urinary protein excretion, inflammatory cell infiltration into the kidney, and renal epithelial-to-mesenchymal transition were all increased.…”
mentioning
confidence: 99%